HUBUNGAN LIFESTYLE DENGAN KEJADIAN HIPERTENSI PADA KEHAMILAN - Anggraini, Arie; Rahmawati, Eka (JURNAL SMART ANKes, 2025)
RELATIONSHIP BETWEEN LIFESTYLE AND HYPERTENSION INCIDENTS IN PREGNANCY Background: Hypertension is one of the complications in pregnancy that can cause morbidity and mortality in both the mother and the fetus she is carrying. According to WHO, hypertension contributes to around 16% of every maternal death in developed countries, while globally an estimated four million pregnant women experience advanced hypertension and around 50,000 to 70,000 mothers die each year due to preeclampsia or advanced hypertension. Indonesia itself, based on data from the 2023 Indonesian Health Survey, reported 3,049 pregnancies with hypertension. South Sumatra contributed 3.1% or around 94 cases of hypertension. A good lifestyle is estimated to be able to minimize the risk of hypertension in pregnancy. Objective: Analyze the relationship between lifestyle and the incidence of hypertension in pregnancy Research Method: Type of analytical survey research, with a cross-sectional approach. Population of 64 pregnant women from January to April 2025, accidental sampling technique. Research instrument in the form of a questionnaire. Data analysis with chi-square. Results: there is a relationship between diet and hypertension in pregnancy with p = 0.013 < 0.05, there is a relationship between rest patterns and the incidence of hypertension with a value of p = 0.021 < 0.05, there is a relationship between exercise patterns and hypertension in pregnancy with a value of p = 0.022 < 0.05. Conclusion: A good lifestyle can reduce the risk of hypertension in pregnancy Suggestion: Good lifestyle counseling as early as possible can help reduce the incidence of hypertension in pregnancy. Keywords: Pregnancy, Lifestyle, Hypertension